Spectrum sensing for cognitive radios - Abu Hanifah, Izyan munyati; Che Rus, Siti Natrah; Jarot, Sigit Puspito Wigati (IIUM Press, 2011)
This chapter discusses about cogmtive radio and the spectrum sensing techniques which is one of the most important issue in cognitive radio. This chapter is organized into two parts: the first part is about the cognitive radio in general, about the definition and the challenges of cognitive radio, and the second part is about spectrum sensing in cognitive radio, including the techniques and the challenges